Determinants of physical activity frequency and provider advice during pregnancy - Eilann C. Santo; Peter W. Forbes; Emily Oken; Mandy B. Belfort (BMC, 2017)
Abstract Background Our aims were to (1) describe the frequency of physical activity and prenatal healthcare provider advice about physical activity during pregnancy and (2) examine determinants and correlates of 3rd trimester physical activity and receipt of physical activity advice. Methods We analyzed data from the 2008 Pregnancy Risk Assessment Monitoring System. We studied 2669 women from North Carolina and Colorado with data on physical activity frequency in the 3 months prior to pregnancy and during the 3rd trimester and 1584 women from Oklahoma with data on provider advice regarding physical activity during pregnancy. Respondents reported physical activity, defined as 30 min or more of exercise/physical activity (excluding vocationally related activity), in in these categories: <1 day/week, 1-4 days/week, and ≥5 days/week. We defined adherence to American College of Obstetrics & Gynecology (ACOG) criteria as physical activity ≥5 days/week in the 3rd trimester. We performed logistic regression analyses weighted for sampling and adjusted for socio-demographic factors. Results Forty-two percent of women in North Carolina and Colorado reported 3rd trimester physical activity <1 day/week, 42% 1-4 days/week, 9% ≥5 days/week; 7% reported being told not to exercise. Seventy-two percent of women in Oklahoma reported receiving physical activity advice from a prenatal care provider. Low activity frequency (<1 day/week) prior to pregnancy was strongly associated with low likelihood of ACOG guideline adherence in the 3rd trimester (aOR 0.10, 95% CU 0.04, 0.30 vs. 1-4 days/week). Underweight women were more likely to adhere to ACOG guidelines than normal weight women (aOR 2.27, 95% CI 1.36, 3.79). Overweight women were more likely to receive physical activity advice (aOR 2.9, 95% CI 1.3, 6.3 vs. normal weight), but obese women were not (aOR 0.65, 95% CI 0.4, 1.2). Conclusions Few women meet ACOG guideline criteria for physical activity during pregnancy. Improving physical activity and weight status prior to pregnancy may improve activity levels during pregnancy. Nearly one third did not receive advice about physical activity during prenatal care. Obese women were no more likely to receive advice than their normal weight counterparts, indicating the need for targeted physical activity counseling in this population.